The Program Evaluation Standards: A Guide for Evaluators and Evaluatio n Users - Yarbrough, Donald B.; Shulha, Lyn M.; Hopson, Rodney K.; Caruthers, Flora A. (SAGE Publications, Inc, 2010)
With oversight from the Joint Committee on Standards for Educational E valuation, Yarbrough, Schulha, Hopson, and Caruthers have revised and illustrated this new edition of the Program Evaluation Standards. Thes e thirty standards support the core attributes of evaluation quality: utility, feasibility, propriety, accuracy, and accountability, and pro vide guidance to anyone interested in planning, implementing, or using program evaluations. The book is an invaluable resource for practicin g evaluators, students, evaluation users, and clients.